Neoliberal governance, sustainable development and local communities in the Barents Region - Tennberg, Monica; Vola, Joonas; Espiritu, Aileen A.; Fors, Bjarge Schwenke; Ejdemo, Thomas; Riabova, Larissa; Korchak, Elena; Tonkova, Elena; Nosova, Tatiana (Luleå tekniska universitet, Samhällsvetenskap, 2014)
There are currently high hopes in the Barents Region for economic growth, higheremployment and improved well-being, encouraged by developments in the energy industry,tourism and mining. The article discusses these prospects from the perspectiveof local communities in five locations in the region, which spans the northernmostcounties of Finland, Norway, Sweden and Northwest Russia. The communities studiedare remote, relatively small, multicultural, and dependent on natural resources. Thesalient dynamic illuminated in the research is how ideas of sustainability and neoliberalgovernance meet in community development. While the two governmentalities oftenconflict, they sometimes also complement one another, posing a paradox that raisesconcerns over the social aspect of sustainable development in particular. The articleis based on international, multidisciplinary research drawing on interviews as well asstatistical and documentary analysis Godkänd; 2014; 20140502 (thoejd)